What’s going around? A social network explanation of youth party membership - Emilien Paulis (Intergenerational Justice Review)
Because people do not join political parties in a social vacuum but rather in close relation with their peers, this paper explores how the structure and composition of interpersonal, social networks affect youth party membership, and questions the answer’s implications for recruitment. The structure does not affect statistically the young citizens’ probability of becoming party members, as the process depends to a high degree on their proximate network core, e.g. their relatives, pointing towards a certain exclusivity in recruitment patterns and giving insight also on why they might stay away from conventional politics. A homogeneous composition matching with a high social and political profile is a pattern that has a considerable impact on their odds of joining a party, stressing that social networks can work in reproducing social and political inequalities, confining recruitment targets to the national population’s most “usual suspects”, and thereby explaining some difficulties faced by party organisations. Drawing on these findings, the conclusion discusses strategic considerations for Belgian parties.